2010
DOI: 10.4141/cjas10022
|View full text |Cite
|
Sign up to set email alerts
|

Bovine biceps femoris is resistant to tenderization by lower-salt moisture enhancement or enzyme addition

Abstract: . Bovine biceps femoris is resistant to tenderization by lower-salt moisture enhancement or enzyme addition. Can. J. Anim. Sci. 90: 495Á503. Unacceptable toughness in retail beef cuts prepared from round muscles is not uncommon. The biceps femoris (BF) muscle is a particular challenge due to its high connective tissue content. Disruption of connective tissue by proteolytic enzyme injection has been demonstrated to improve tenderness in some muscles. Moisture enhancement can also be effective; however, concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It has been reported (Baublits, Pohlman, Brown, Yancey, & Johnson, 2006;Kolle, McKenna, & Savell, 2004;Pietrasik & Shand, 2010) that moisture enhancement is less effective for improving tenderness in BF steaks, and these authors suggested that the relatively large amount of collagen in the BF may have contributed to the lack of effect of moisture enhancement.…”
Section: Wbsfmentioning
confidence: 93%
“…It has been reported (Baublits, Pohlman, Brown, Yancey, & Johnson, 2006;Kolle, McKenna, & Savell, 2004;Pietrasik & Shand, 2010) that moisture enhancement is less effective for improving tenderness in BF steaks, and these authors suggested that the relatively large amount of collagen in the BF may have contributed to the lack of effect of moisture enhancement.…”
Section: Wbsfmentioning
confidence: 93%
“…These changes might result from the increased number of water binding sites being exposed increasing interaction between protein and water (Xiong, 2005;Zhang et al, 2017). Other study by Pietrasik and Shand (2010) found that the cooking loss of beef was decreased with the treatment by purified papain. Chaurasiya et al, (2015) also found that the 162.0 U/g purified bromelain reduced the cooking loss of beef from 49.7% (the control) to 47.2%.…”
Section: Physiochemical Analysismentioning
confidence: 98%